Dreams Deferred: The Impact of Sexual Assault during Adolescence on the Educational Outcomes and Life Choices of Women - Andrea B. Nikischer (Adult Education Research Conference, 2014)
This paper explores the impact of sexual assault on the educational outcomes and life choices of women. Findings indicate that sexual assault during adolescence negatively impacts movement through the life pipeline in adulthood. Best practices for addressing sexual violence in adult education are discussed, and recommendations for future research are offered.